English curricular adaptation and special educational needs grade 3, in third grade EGB students at Unidad Educativa Particular Bilingüe Sagrados Corazones during the school year 2019-2020 - Rodríguez González, Paul Andrés (2020)
In our society, Education is an inalienable right. However, there is still an important portion of the population that has no access to the educational system, and other portion even more important, that is excluded because of their special capacities or have special needs they were born with. One of the most important challenges a teacher faces is the lack of curricular adaptation models for this kind of students, which is the result of little interest in curricular strategies to benefit the vulnerable population. The current study focuses on Unidad Educativa Particular Bilingue “Sagrados Corazones”, which shows the necessity of fulfil the appropriate standards of curricular adaptation for Special Educational Needs, grade 3, who are not being addressed correctly in content and learning skills. The current study proposes the elaboration of a specific curriculum adaptation with the purpose of having a well-structured set of activities to fulfill those cognitive gaps in their second language acquisition and ensure that the content and learning they are receiving is the adequate one suited for their level in English………..